Universality of Torpor Expression in Bats - Fjelldal, Mari Aas; Sørås, Rune; Stawski, Clare (Zenodo, 2022)
(Uploaded by Plazi for the Bat Literature Project) Although heterothermy is employed by species at a global level within the order of Chiroptera (bats), the possibility of torpor being expressed in bat species inhabiting warmer climate zones has been explored only in the past couple decades. Recent studies suggest that the benefit of expressing torpor is not limited to saving energy during cold exposure or food shortage but may be just as important for saving water during heat waves. Thus, even if the physiological challenges faced by bats may depend on the habitat they live in, species expressing torpor should be found in any climate zone where employing torpor may yield benefits and increase their survival probability. Here, we summarize available data on torpor metabolic rates and daily skin temperature patterns of bats across climate zones, emphasizing similarities found in the data. We also present data that we have collected from a southern subtropical species (Nyctophilus bifax) and a northern subarctic species (Plecotus auritus) to illustrate specific examples of torpor expressions in two bat species living in highly different environments. Our findings highlight that torpor metabolic rates and skin temperature patterns of bats outside of the hibernation season can be universal across vastly different habitats, although arid environments indicate potential divergence in mean minimum torpor metabolic rates compared with measurements of populations inhabiting other climate zones.